In vitro study of effectiveness of saponin from Sapindus rarak fruit as methanogenesis inhibitor on ruminal digestion system - Amlius Thalib (Indonesian Center for Animal Research and Development (ICARD), 2004)
Methane produced in the rumen system causes the lost of ingested chemical energy, and the methane emitted contributes the greenhouse effect to the atmosphere environment. A study to evaluate the effectiveness of saponin from Sapindus rarak fruit as an inhibitor of ruminal methanogenesis was conducted. The method conducted in this study was a fermentation of a substrate by in vitro technique using rumen fluid (obtained from fistulated sheep) as inoculum. Substrate (king grass) was fermented in anaerobic incubator system at pH of medium 6.9 and temperature of 39°C for 48 hours. Inoculum was supplemented with an ingredient obtained by extraction of Sapindus rarak fruit with methanol (Aksapon SR) and the ones without extraction (lerak powder), and further, these treatments were compared to other methanogenesis inhibitors (i.e. Fe3+, SO4 2– and poly unsaturated longchain fatty acids: PULCFA).The treatments were 1). Inoculum without treatment (K); 2). K + Aksapon SR (80 mg/100 ml); 3). K + lerak powder (160 mg/100 ml); 4). K + Fe3+ (0.8 mg/100 ml); 5. K + SO4 2- (96 mg/100 ml); 6). K + PULCFA (24 mg/100 ml). Measurements conducted were portion of methane, dry matter digestibility (DMD), NH3-N content, microbial population, and volatile fatty acids (VFA). The data measured were analyzed by using completely randomized design. The results of the experiment showed that Aksapon SR was the most effective inhibitor of methanogenesis compared to the others, that is when compared to control, Aksapon SR lowered methane production by 31% (P<0.01), and followed by treatments of Fe3+ (22%) (P<0.05), lerak powder (21%) (P<0.05), PULCFA (11%) (P>0.05) and SO4 2–(10%) (P>0.05). All additive treatments did not affect the DMD value of the substrate fermented by control inoculum. Compared to control, all treatments lowered the protozoal population where the Aksapon SR gave the strongest effect (1.91 x 105 vs 9.94 x 105 cell/ml), and the decrease of protozoal number in Aksapon SR treatment was followed by the increase of bacterial (4.13 x 109 vs 2.56 x 109 colony/ml). Aksapon SR and SO4 2- did not influence the total VFA production, while lower VFA productions were found on lerak powder and Fe3+ treatments (P<0.05), and the reverse effect was shown by PULCFA (P<0.05). Acetate/propionate ratio was significantly changed by Aksapon SR and lerak powder treatments (i.e. 1.37 and 1.33 respectively, vs 2.20). In conclusion, Aksapon SR was the most effective methanogenesis inhibitor compared to the others used in this study, and saponin contained in Sapindus rarak fruit could also be used as propionate enhancer. Key words: Saponin, Sapindus rarak, methanogenesis, inhibitor